A Neural Mechanism of Preference Shifting Under Zero Price Condition - Votinov, Mikhail; Aso, Toshihiko; Fukuyama, Hidenao; Mima, Tatsuya (Frontiers in Human Neuroscience, 2016)
In everyday life, free products have a strong appeal to us, even if we do not need them. Behavioral studies demonstrated that people have a tendency to switch their preference from preferred more expensive products to less preferable, cheaper alternatives, when the cheaper option becomes free. However, the neural representation of this behavioral anomaly called “zero price” is still unclear. Using fMRI, we studied subjects while they performed binary preference choice task for items with different prices. We found that zero-related change of preference was associated with activation of the choice network, which includes inferior parietal lobule, posterior cingulate cortex and medial prefrontal cortex. Moreover, the amount of activation in medial prefrontal cortex was positively correlated with the subjective happiness score of getting free products. Our findings suggest that the zero price effect is driven by affective evaluations during decision-making.